Factors Influencing Employee Productivity in Work From Anywhere: A Systematic Literature Review (SLR) - Fauziyah, Neyla Neyla Nuril; Priharsari, Diah; Pinandito, Aryo; Pradana, Fajar (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
Many companies have begun to adopt both ways of working simultaneously or commonly referred to as Work From Anywhere (WFA); it is necessary to model business processes used to evaluate and improve the WFA work system in the future. In modelling business processes, it is necessary to carry out a needs analysis, one of which is to find out what factors affect employee productivity when doing their work. Several research journals related to WFA work productivity factors are still scattered in various journal databases, so it is necessary to unify them from various journals. Therefore, it is necessary to research the grouping of factors and theories that affect the productivity of WFA employees in the Systematic Literature Review (SLR) method. Before grouping, the search criteria and journal search process are determined first. The first search is to identify based on keywords, year of publication, and journal quality. Then continued, the use of Cohen's Kappa method for selection based on the field of discussion and language, abstracts, and contents. In improving the reliability of the library screening results, each selection is made twice (or more) and calculates the value of Cohen's Kappa. The SLR method makes the usually subjective literature study more objective to reduce the researcher's bias. The results obtained were a total of 17 screening journals with a total of 11 factors, namely environment, time efficiency, psychology, health, cost efficiency, employee personality, adequate technology, gender, geographical flexibility, salary, and communication.